Comparisons of microsomal cytochrome P450 content and enzymatic activity towards selected model substrates and insecticides in different tissues from the migratory locust (Locusta migratoria). (October 2018) - Liu, Jiao; Zhang, Xueyao; Wu, Haihua; Gao, Yue; Silver, Kristopher; Ma, Enbo; Zhang, Jianzhen; Zhu, Kun Yan
Abstract: Cytochrome P450 monooxygenases (P450s) are important enzymes for biotransformations of various endogenous and xenobiotic substances in various organisms. In this study, we examined microsomal P450 protein content and enzymatic activity in four major detoxification tissues dissected from fifth-instar nymphs of the migratory locust ( Locusta migratoria ). The highest microsomal P450 protein content was found in the gastric caeca (a part of the midgut), followed by the midgut, Malpighian tubules and fat bodies. Microsomal P450s showed the highest aromatic hydroxylation, O -dealkylation and O -dearylation activities towards six of the seven model substrates examined in the fat bodies. Although the gastric caeca showed the highest P450 protein content, the enzymatic activities towards six of the seven model substrates were the lowest in this tissue. Further, the midgut, gastric caeca and fat bodies showed significant metabolic activities towards two pyrethroid insecticides (deltamethrin and fluvalinate), but no significant activities towards the other four insecticides (malathion, chlorpyrifos, carbaryl and methoprene). These results support our conclusions: 1) total P450 protein content alone cannot be reliably used to predict its enzymatic activity, and 2) insect P450 enzymatic activity is both tissue and substrate dependent. Graphical abstract: Image 1 Highlights: Microsomal P450 content was highest in gastric caeca and lowest in fat bodies. P450 activity measured on seven substrates was different in different tissues. Pyrethroids were metabolized by P450s, but four other insecticides were not. P450 activity cannot be used as a measure of insecticide detoxification potential.